Tectorigenin Alleviates Inflammation, Apoptosis, and Ossification in Rat Tendon-Derived Stem Cells via Modulating NF-Kappa B and MAPK Pathways - Moqbel, Safwat Adel Abdo; Xu, Kai; Chen, Zhonggai; Xu, Langhai; He, Yuezhe; Wu, Zhipeng; Ma, Chiyuan; Ran, Jisheng; Wu, Lidong; Xiong, Yan (Frontiers in Cell and Developmental Biology, 2020)
Tendinopathy is a common musculoskeletal disorder that mainly affects athletes and people of older age. Tumor necrosis factor-α (TNF-α) plays an important role in initiating tendinopathy. Tectorigenin, an extract component of Belam-canda Chinesis, possesses anti-inflammatory and anti-apoptosis activity. The present study was established to investigate the role of tectorigenin against the pathogenetic effects of TNF-α on tendon-derived stem cells (TDSCs) in vivo and in vitro. The findings indicated that TNF-α is able to induce TDSC inflammation, apoptosis, and ossification, as well as activate nuclear factor-kappa B and mitogen-activated protein kinase (MAPK). Furthermore, the results confirmed that tectorigenin is able to inhibit the TNF-α-induced inflammation, apoptosis, and ossification. Tectorigenin treatment decreases activation of NF-kappa B and MAPK signaling in TDSCs. Tectorigenin ameliorates tendinopathy in the in vivo rat model. Thus, these data reveal that tectorigenin can serve as a potential treatment for tendinopathy.